Compatibility of Commonly Used Active Pharmaceutical Ingredients in a Ready-to-Use Oral Suspending Vehicle - Mercedeh Mansourian; Eli Dijkers; Carolina C. V. Silva; Hudson C. Polonini (MDPI AG, 2023)
The present study aimed to evaluate the stability of active pharmaceutical ingredients (APIs) from different pharmacological classes in a compounded oral suspending vehicle. Oral suspensions of amoxicillin trihydrate (50 mg/mL), clozapine (25 mg/mL), indomethacin (5.0 mg/mL), levodopa/carbidopa (10.0/2.5 mg/mL), levothyroxine sodium (T4, 25 µg/mL), lomustine (4.0 and 10.0 mg/mL), methyldopa (25 mg/mL) and procarbazine (10.0 mg/mL) were formulated in SyrSpend® SF PH4 and the stability was monitored for up to 90 days, except for amoxicillin trihydrate, which was evaluated for 30 days only. The APIs' stability was determined by measuring percent recovery using stability-indicating high-performance liquid chromatography (HPLC or UHPLC) or titration (amoxicillin trihydrate only). The stability of amoxicillin trihydrate, clozapine, indomethacin and levodopa/carbidopa were studied at both refrigerated (2-8 °C) and room temperature (20-25 °C). Lomustine, procarbazine, and methyldopa were studied at refrigerated temperature only. Our data demonstrated promising stability for the compounded suspensions containing various APIs, investigated in SyrSpend® SF PH4, as all APIs exhibited stability throughout the study duration and met content uniformity criteria. These findings lead to the conclusion that the tested compounded oral suspensions present a viable approach for creating personalized, age-appropriate formulations. The capacity to ensure dose consistency and stability using APIs from diverse pharmacological classes renders them suitable choices for both pediatric and geriatric patients.